1991
DOI: 10.1099/00221287-137-12-2681
|View full text |Cite
|
Sign up to set email alerts
|

An IS1-like element is responsible for high-level synthesis of extended-spectrum  -lactamase TEM-6 in Enterobacteriaceae

Abstract: Resistance of Escherichiu coli strain HB251 to the newer p-lactam antibiotics, in particular ceftazidime and aztreonam, results from production of the extended-spectrum p-lactamase TEM-6. The corresponding structural gene, bfuT-6, and its promoter region were amplified by the polymerase chain reaction. Analysis of the sequence of the amplification product showed that bluT-6 differed by two nucleotide substitutions from bluT-1, the gene encoding TEM-1 penicillinase in plasmid pBR322. The mutations led to the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 35 publications
0
32
0
1
Order By: Relevance
“…In the DNA sequence upstream of bla ABA-1 , a putative hybrid promoter consisting of a Ϫ35 promoter located in the inverted repeat of ISOur1 and a Ϫ10 promoter sequence that may correspond to part of the original promoter sequence of a cephalosporinase gene of A. baumannii was evidenced. Hybrid promoters containing a Ϫ35 promoter region located in the inverted repeat of the IS6 family of IS elements have been reported for bla in Klebsiella pneumoniae (15) and bla SHV-2a in P. aeruginosa (28). Target site duplication that results from a transposition event was not found immediately downstream or upstream of ISOur1, suggesting that ISOur1 and bla ABA-1 may have been cotransferred from A. baumannii.…”
Section: Discussionmentioning
confidence: 99%
“…In the DNA sequence upstream of bla ABA-1 , a putative hybrid promoter consisting of a Ϫ35 promoter located in the inverted repeat of ISOur1 and a Ϫ10 promoter sequence that may correspond to part of the original promoter sequence of a cephalosporinase gene of A. baumannii was evidenced. Hybrid promoters containing a Ϫ35 promoter region located in the inverted repeat of the IS6 family of IS elements have been reported for bla in Klebsiella pneumoniae (15) and bla SHV-2a in P. aeruginosa (28). Target site duplication that results from a transposition event was not found immediately downstream or upstream of ISOur1, suggesting that ISOur1 and bla ABA-1 may have been cotransferred from A. baumannii.…”
Section: Discussionmentioning
confidence: 99%
“…In E. coli HB251, a 116-bp insert with similarity to IS1 was found to have inserted in the native promoter region of the blaT-6 gene encoding TEM-6 ,-lactamase. The original -10 region was retained, and the new -35 sequences were provided by the ISl-like element, increasing activity of the promoter 10-fold (10).…”
Section: Discussionmentioning
confidence: 99%
“…Primers (400 pmol of 5' ends) were labeled with [y-32P]ATP, and 105 cpm (0.045 ,uCi) of oligonucleotide was precipitated with total RNA (up to 50 ,ug for high-activity strains and 100 ,ug for low-activity strains) in diethyl pyrocarbonate-treated tubes. The resulting pellet was dried, resuspended in hybridization buffer {80% formamide, 0.4 M NaCl, 1 mM EDTA (pH 8), 40 mM PIPES [piperazine-N,N'-bis-(2-ethanesulfonic acid); pH}, incubated at 85°C for 10 min, and then annealed overnight (8)(9)(10)(11)(12) 25285, cepA85-L, U05887; CS14, cepA14-L, U05883; CS29, cepA29 L, U05884; and CS44, cepA44-L, U05885.…”
mentioning
confidence: 99%
“…Consequently, it came as an unwelcome surprise when a species of Klebsiella with plasmid-mediated resistance to extended-spectrum cephalosporins was isolated in Germany in 1983, and in the following year, similar resistance in Klebsiella was reported from France. It was found that in the former case, the resistance was due to a new â-lactamase that differed from the enzyme SHV-1 by a single mutation, and was therefore named SHV-2 (Goussard et al, 1991). The enzyme detected in France was named CTX-1, and was found to be a mutant TEM enzyme (Sirot et al, 1987).…”
Section: Introductionmentioning
confidence: 99%